Digital tools for qualitative research - Paulus, Trena M.; Lester, Jessica Nina; Dempster, Paul G. (SAGE, 2014)
Digital Tools for Qualitative Research shows how the research process in its entirety can be supported by technology tools in ways that can save time and add robustness and depth to qualitative work. It addresses the use of a variety of tools (many of which may already be familiar to you) to support every phase of the research process, providing practical case studies taken from real world research.